2020
DOI: 10.1007/s10980-020-01037-1
|View full text |Cite
|
Sign up to set email alerts
|

Land use change drives the spatio-temporal variation of ecosystem services and their interactions along an altitudinal gradient in Brazil

Abstract: Context Land use and land cover (LULC) changes may affect the provision of ecosystem services. However, little is known how LULC changes influence the spatio-temporal variation in ecosystem service and their interactions along altitudinal gradients. Objectives Here we assessed the spatio-temporal variation of eight ecosystem services in an altitudinal gradient between the year of 1986 and 2015, and quantified the effect of LULC transitions on the provision and interactions of ecosystems services. Methods We mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 64 publications
(60 reference statements)
0
38
0
Order By: Relevance
“…Biophysical conditions, including temperature, precipitation, evapotranspiration, soil type, and ultimately vegetation type, can vary dramatically in mountain systems [16]. Therefore, the spatial heterogeneity of ESs is high [17]. However, we still have a limited understanding of how to construct landscape units to reflect spatial heterogeneity and how provisioning patterns of multiple ESs emerge and change in space and time along the landscape and terrain gradients in mountain systems.…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical conditions, including temperature, precipitation, evapotranspiration, soil type, and ultimately vegetation type, can vary dramatically in mountain systems [16]. Therefore, the spatial heterogeneity of ESs is high [17]. However, we still have a limited understanding of how to construct landscape units to reflect spatial heterogeneity and how provisioning patterns of multiple ESs emerge and change in space and time along the landscape and terrain gradients in mountain systems.…”
Section: Introductionmentioning
confidence: 99%
“…High demands for food, timber, energy, housing, and other goods and services to meet the demands of more than 7 billion people worldwide—as well as the shifts in land management efforts to enhance some ES but at the cost of reductions in many ES—have resulted in the degradation of global ecosystem services at unprecedented intensities and rates [ 3 ]. Among all human activities, land-use and land-cover change (LUCC) is always the significant factor affecting the composition and configuration of ecosystems that leads to a change in the provision of ecosystem services [ 2 , 4 , 5 ], as some ES are closely related to specific land-use types [ 6 ]. For example, the conversion of grasslands, forests, and water areas into croplands and developed areas has led to a substantial increase in the production of food, housing, and other commodities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, to effectively evaluate the impacts of land-use change on ES, we linked the GeoSOS-FLUS (Sun Yat-sen University, Guangzhou, China) and InVEST (Integrated Valuation of Ecosystem Service and Tradeoffs) models (Stanford University, Palo Alto, CA, USA), which are both suitable for application under different scenarios [ 6 , 8 , 30 ]. The GeoSOS-FLUS model was used to quantify the changes in land-use between the years 2000, 2015, and 2030, under three scenarios: (1) Business As Usual (BAU), (2) Rapid Urban Development (RUD), and (3) Ecological Protection (ELP).…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of land dynamics requires the detection of LULC changes [22]. Empirical studies by researchers from various disciplines have shown that changes in LULC are key to various applications, such as hydrology, agriculture, forestry, the environment, geology, and ecology [1,2,23,24]. Many researchers argue that LULC change could result in an ecosystem imbalance and impacts on the environment caused by humans and their role in climate change [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%